La no evidencia de la “evidence". A veinte años del inicio de su uso. - Vázquez-Benítez, Efraín (Ginecología y Obstetricia de México)
In view of the widespread wrong use in spanish of the erroneous translation of Evidence-based Medicine as “medicina basada en la evidencia", comments are made from the general concepts of phylosophy, particularly from the chapter of “semiotics", which demonstrate the fallacious use of such a wrong translation and the dangers of its indiscriminate use of this procedure, that may be very valuable in its methodology as proposed by its founders and understood by englsh-speaking physicians, making emphasis in the fact that it is just a method to obtain a better level of certainty and not a system that should replace the criteria employed in traditional medicine. Examples are offered of several serious mistakes that have been made by the erroneous application of results offered even in articles published in english. Finally, a review is made of articles published in five prestigious journals and the difficulty of interpreting their contents as a source of clinically useful information. A novel procedure is proposed as a possible alternative for assessing medical literature.